Involvement of Vanin-1 in Ameliorating Effect of Oxidative Renal Tubular Injury in Dahl-Salt Sensitive Rats - Hosohata, Keiko (Int J Mol Sci, 2019)
In salt-sensitive hypertension, reactive oxygen species (ROS) play a major role in the progression of renal disease partly through the activation of the mineralocorticoid receptor (MR). We have previously demonstrated that urinary vanin-1 is an early biomarker of oxidative renal tubular injury. However, it remains unknown whether urinary vanin-1 might reflect the treatment effect. The objective of this study was to clarify the treatment effect for renal tubular damage in Dahl salt-sensitive (DS) rats. DS rats (six weeks old) were given one of the following for four weeks: high-salt diet (8% NaCl), high-salt diet plus a superoxide dismutase mimetic, tempol (3 mmol/L in drinking water), high-salt diet plus eplerenone (100 mg/kg/day), and normal-salt diet (0.3% NaCl). After four-week treatment, blood pressure was measured and kidney tissues were evaluated. ROS were assessed by measurements of malondialdehyde and by immunostaining for 4-hydroxy-2-nonenal. A high-salt intake for four weeks caused ROS and histological renal tubular damages in DS rats, both of which were suppressed by tempol and eplerenone. Proteinuria and urinary N-acetyl-β-D-glucosaminidase exhibited a significant decrease in DS rats receiving a high-salt diet plus eplerenone, but not tempol. In contrast, urinary vanin-1 significantly decreased in DS rats receiving a high-salt diet plus eplerenone as well as tempol. Consistent with these findings, immunohistochemical analysis revealed that vanin-1 was localized in the renal proximal tubules but not the glomeruli in DS rats receiving a high-salt diet, with the strength attenuated by tempol or eplerenone treatment. In conclusion, these results suggest that urinary vanin-1 is a potentially sensitive biomarker for ameliorating renal tubular damage in salt-sensitive hypertension.